A ParDE toxin–antitoxin system is responsible for the maintenance of the Yersinia virulence plasmid but not for type III secretion-associated growth inhibition - Schott, Saskia; Scheuer, Robina; Ermoli, Francesca; Glatter, Timo; Evguenieva-Hackenberg, Elena; Diepold, Andreas (Frontiers in Cellular and Infection Microbiology, 2023)
Many Gram-negative pathogens utilize the type III secretion system (T3SS) to translocate virulence-promoting effector proteins into eukaryotic host cells. The activity of this system results in a severe reduction of bacterial growth and division, summarized as secretion-associated growth inhibition (SAGI). In Yersinia enterocolitica, the T3SS and related proteins are encoded on a virulence plasmid. We identified a ParDE-like toxin–antitoxin system on this virulence plasmid in genetic proximity to yopE, encoding a T3SS effector. Effectors are strongly upregulated upon activation of the T3SS, indicating a potential role of the ParDE system in the SAGI or maintenance of the virulence plasmid. Expression of the toxin ParE in trans resulted in reduced growth and elongated bacteria, highly reminiscent of the SAGI. Nevertheless, the activity of ParDE is not causal for the SAGI. T3SS activation did not influence ParDE activity; conversely, ParDE had no impact on T3SS assembly or activity itself. However, we found that ParDE ensures the presence of the T3SS across bacterial populations by reducing the loss of the virulence plasmid, especially under conditions relevant to infection. Despite this effect, a subset of bacteria lost the virulence plasmid and regained the ability to divide under secreting conditions, facilitating the possible emergence of T3SS-negative bacteria in late acute and persistent infections.